Whole-Genome-Sequence-Based Characterization of Extensively Drug-Resistant Acinetobacter baumannii Hospital Outbreak - Ghiwa Makke (American Society for Microbiology, 2020)
ABSTRACT Carbapenem-resistant Acinetobacter baumannii (CRAB) is an important opportunistic pathogen linked to a variety of nosocomial infections and hospital outbreaks worldwide. This study aimed at investigating and characterizing a CRAB outbreak at a large tertiary hospital in Lebanon. A total of 41 isolates were collected and analyzed using pulsed-field gel electrophoresis (PFGE). Whole-genome sequencing (WGS) was performed on all the isolates, and long-read PacBio sequencing was used to generate reference genomes. The multilocus sequence types (MLST), repertoire of resistance genes, and virulence factors were determined from the sequencing data. The plasmid content was analyzed both in silico and using the A. baumannii PCR-based replicon typing (AB-PBRT) method. Genome analysis initially revealed two clones, one carrying blaOXA-23 on Tn2006 (ST-1305, ST-195, and ST-218) and another carrying blaOXA-72 on pMAL-1 (ST-502 and ST-2059, a new ST), with the latter having two subclones, as revealed using the Bayesian transmission network. All isolates were extensively drug resistant (XDR). WGS analysis revealed the transmission pathways and demonstrated the diversity of CRAB isolates and mobile genetic elements in this health care setting. Outbreak detection using WGS and immediate implementation of infection control measures contribute to restraining the spread and decreasing mortality. IMPORTANCE Carbapenem-resistant Acinetobacter baumannii (CRAB) has been implicated in hospital outbreaks worldwide. Here, we present a whole-genome-based investigation of an extensively drug-resistant CRAB outbreak rapidly spreading and causing high incidences of mortality at numerous wards of a large tertiary hospital in Lebanon. This is the first study of its kind in the region. Two circulating clones were identified using a combination of molecular typing approaches, short- and long-read sequencing and Bayesian transmission network analysis. One clone carried blaOXA-23 on Tn2006 (ST-1305, ST-195, and ST-218), and another carried blaOXA-72 on a pMAL-1 plasmid (ST-502 and ST-2059, a new ST). A pMAL-2 plasmid was circulating between the two clones. The approaches implemented in this study and the obtained findings facilitate the tracking of outbreak scenarios in Lebanon and the region at large.